Regulation of PKD2 channel function by TACAN. (13th December 2022) - Liu, Xiong; Zhang, Rui; Fatehi, Mohammad; Wang, Yifang; Long, Wentong; Tian, Rui; Deng, Xiaoling; Weng, Ziyi; Xu, Qinyi; Light, Peter E.; Tang, Jingfeng; Chen, Xing‐Zhen
Abstract : Abstract: Autosomal dominant polycystic kidney disease is caused by mutations in the membrane receptor PKD1 or the cation channel PKD2. TACAN (also termed TMEM120A), recently reported as an ion channel in neurons for mechanosensing and pain sensing, is also distributed in diverse non‐neuronal tissues, such as kidney, heart and intestine, suggesting its involvement in other functions. In this study, we found that TACAN is in a complex with PKD2 in native renal cell lines. Using the two‐electrode voltage clamp in Xenopus oocytes, we found that TACAN inhibits the channel activity of PKD2 gain‐of‐function mutant F604P. TACAN fragments containing the first and last transmembrane domains interacted with the PKD2 C‐ and N‐terminal fragments, respectively. The TACAN N‐terminus acted as a blocking peptide, and TACAN inhibited the function of PKD2 by the binding of PKD2 with TACAN. By patch clamping in mammalian cells, we found that TACAN inhibits both the single‐channel conductance and the open probability of PKD2 and mutant F604P. PKD2 co‐expressed with TACAN, but not PKD2 alone, exhibited pressure sensitivity. Furthermore, we found that TACAN aggravates PKD2‐dependent tail curvature and pronephric cysts in larval zebrafish. In summary, this study revealed that TACAN acts as a PKD2 inhibitor and mediates mechanosensitivity of the PKD2–TACAN channel complex. Key points: TACAN inhibits the function of PKD2 in vitro and in vivo . TACAN N‐terminal S1‐containing fragment T160X interacts with the PKD2 C‐terminal fragment N580–L700, and its C‐terminal S6‐containing fragment L296–D343 interacts with the PKD2 N‐terminal A594X. TACAN inhibits the function of the PKD2 channel by physical interaction. The complex of PKD2 with TACAN, but not PKD2 alone, confers mechanosensitivity. Abstract : Abstract figure legend PKD2 is a Ca 2+ ‐permeable cation channel and is mutated in ∼15% of cases of human autosomal dominant polycystic kidney disease. Using the two‐electrode voltage clamp with Xenopus oocytes, patch clamp with mammalian cells, the zebrafish model and molecular biology techniques, we have found that the membrane protein TACAN forms a complex with PKD2 on the primary cilia of renal epithelial cell lines and acts as an inhibitor of the function of PKD2 in vitro and in vivo .